Efficacy and Safety of Aclidinium/Formoterol versus Tiotropium in COPD: Results of an Indirect Treatment Comparison - Medic, Goran (Adv Ther, 2016)
INTRODUCTION: The objective of this study was to estimate the relative efficacy and safety of fixed-dose combination aclidinium/formoterol 400/12 μg twice daily compared to tiotropium 18 μg once daily in adult patients with moderate-to-severe chronic obstructive pulmonary disease (COPD). METHODS: A systematic literature review performed in March 2014, using a predefined search strategy in MEDLINE, EMBASE and Cochrane Library, identified 17 randomized placebo-controlled trials, (tiotropium n = 15; aclidinium/formoterol n = 2). Outcomes of interest were: bronchodilation (peak and trough forced expiratory volume in 1 s (FEV(1))), COPD symptoms [Transition Dyspnea Index (TDI) focal score and % of responders (>1 unit improvement)] and Health Related Quality of Life (HRQoL) [St. George’s Respiratory Questionnaire (SGRQ) total score and % responders (>4 unit improvement)], % of patients with ≥1 exacerbations, adverse events (AE), serious adverse events (SAE), hospitalization and mortality, all at 24 weeks. In the absence of head-to-head trials between aclidinium/formoterol and tiotropium, a Bayesian indirect treatment comparison (ITC) was used with placebo as common control. RESULTS: Regarding bronchodilation, aclidinium/formoterol was found to be more efficacious than tiotropium at peak FEV(1), with mean difference in change from baseline (DCFB) 143 mL [95% credible interval (CrI): 112, 174] and at trough FEV(1) [DCFB 26 mL (95% CrI −2, 55)]. Aclidinium/formoterol is expected to be more efficacious than tiotropium in improving dyspnea symptoms measured by TDI [DCFB 0.54 points (95% CrI 0.09, 0.99); odds ratio (OR) of responders 1.51 (95% CrI 1.11, 2.06)]. SGRQ results are comparable for aclidinium/formoterol versus tiotropium [DCFB −0.52 (95% CrI −2.21, 1.17); OR of responders 1.16 (95% CrI 0.47, 2.87)]. The ITC results suggest similar safety profiles regarding AEs, SAEs and hospitalization. CONCLUSION: Based on the ITC, aclidinium/formoterol is expected to be more efficacious than tiotropium in terms of lung function and symptom control while providing comparable HRQoL results and safety profile. FUNDING: AstraZeneca. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12325-016-0299-4) contains supplementary material, which is available to authorized users.